RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PENGELOLAAN ROTI BAKAR MENGGUNAKAN METODE WATERFALL (Studi Kasus Waena Perumnas III Kota Jayapura) - Helson Matuan; Yusuf Patay, Esau Dude, Atius Mallo, Emy Lenora Tatuhey (ADISAM PUBLISHER, 2026)
The toast business in the Waena Perumnas III area, Jayapura City, is still using a manual management system in its operational activities, such as recording sales, managing menus, and compiling payment reports. This conventional process often causes various obstacles, such as recording errors, late reports, and difficulties in monitoring stock. This study aims to design and build a web-based management information system that can help facilitate the management of the toast business to be more efficient and organized. The method used in developing the system is Waterfall, which consists of the stages of needs analysis, design, implementation, and testing. This system provides features for managing sales data, raw material stock, and transaction reports, and can only be accessed by admins and cashiers. It is hoped that with this system, the operational process of the toast business will be faster, more accurate, and more integrated.